Post-marketing withdrawal of anti-obesity medicinal products because of adverse drug reactions: a systematic review. - Onakpoya, I; Heneghan, C; Aronson, J (BioMed Central, 2016)
Background We identified anti-obesity medications withdrawn since 1950 because of adverse drug reactions after regulatory approval, and examined the evidence used to support such withdrawals, investigated the mechanisms of the adverse reactions, and explored the trends over time. Methods We conducted searches in PubMed, the World Health Organization database of drugs, the websites of drug regulatory authorities, and selected full texts, and we hand searched references in retrieved documents. We included anti-obesity medications that were withdrawn between 1950 and December 2015 and assessed the levels of evidence used for making withdrawal decisions using the Oxford Centre for Evidence-Based Medicine criteria. Results We identified 25 anti-obesity medications withdrawn between 1964 and 2009; 23 of these were centrally acting, via monoamine neurotransmitters. Case reports were cited as evidence for withdrawal in 80% of instances. Psychiatric disturbances, cardiotoxicity (mainly attributable to re-uptake inhibitors), and drug abuse or dependence (mainly attributable to neurotransmitter releasing agents) together accounted for 83% of withdrawals. Deaths were reportedly associated with seven products (28%). In almost half of the cases, the withdrawals occurred within 2 years of the first report of an adverse reaction. Conclusions Most of the drugs that affect monoamine neurotransmitters licensed for the treatment of obesity over the past 65 years have been withdrawn because of adverse reactions. The reasons for withdrawal raise concerns about the wisdom of using pharmacological agents that target monoamine neurotransmitters in managing obesity. Greater transparency in the assessment of harms from anti-obesity medications is therefore warranted.